KEJADIAN SINDROM OBSTRUKSI PASCA TUBERKULOSIS DI RSU DR. SOEDARSO PONTIANAK PERIODE 1 JANUARI 31 DESEMBER 2010 - ., Anastasia Irawati (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Most commonly found of sequelae on patients with post tuberculosis(TB) is Obstruction Syndrome Post TB (OSPT), which can interfere withquality of life and causes death by 15% after duration of 10 years. Thisdescriptive study with cross sectional design was aimed to determine theincident rate of OSPT at dr. Soedarso Pontianak Hospital on periodJanuary 1 December 31, 2010 based on pulmonary functional test withpeak flow meter. Found as many as 37 samples with OSPT from 99samples with post TB which can be studied, with incident rate of 37,4%.Incident of OSPT found more common in elderly group (54,1%), males(41,9%), and patients who reside in the subdistrict of East Pontianak, andno significant differences in outcome to the span of time between whenthey are deemed post TB and when pulmonary functional testperformed.Keywords : Post TB, OSPTNotes:1. Medical School, Faculty of Medicine, Tanjungpura University,Pontianak, West Borneo, e-mail: dr.anastasia_irawati@yahoo.com32. Department of Pulmonology, RSU dr. Soedarso, Pontianak, West Borneo3. Department of Parasitology, Faculty of Medicine, TanjungpuraUniversity, Pontianak, West Borneo